2005
DOI: 10.1002/ird.164
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation water saving by management of existing subsurface drainage in Egypt

Abstract: Egypt is faced with a water scarcity situation due to increasing demands on a fixed resource which could limit the country's ability to further its overall economic development. There is a danger that farmers in the Nile Valley and Delta may receive less irrigation water and of lower average quality in the future if no actions are taken towards irrigation water saving.In Egypt more than 2 million ha have a subsurface drainage system. These systems have been designed with fixed drain depths and spacings to meet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 5 publications
2
11
0
Order By: Relevance
“…This provides drainage during wet periods, but utilizes control structures to manage the water level in the drainage outlet, making it possible to reduce over‐drainage and increase water use efficiency (Osmond et al ., ). Controlled drainage has also been recognized as the best management practice to reduce the transport and delivery of nitrogen and phosphorus to sensitive surface waters, and many studies have shown that controlled drainage can improve drainage water quality when properly designed and carefully managed (Wesström et al ., ; Ng et al ., ; Dukes et al ., ; Khan et al ., ; Wahba et al ., ; Luo et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…This provides drainage during wet periods, but utilizes control structures to manage the water level in the drainage outlet, making it possible to reduce over‐drainage and increase water use efficiency (Osmond et al ., ). Controlled drainage has also been recognized as the best management practice to reduce the transport and delivery of nitrogen and phosphorus to sensitive surface waters, and many studies have shown that controlled drainage can improve drainage water quality when properly designed and carefully managed (Wesström et al ., ; Ng et al ., ; Dukes et al ., ; Khan et al ., ; Wahba et al ., ; Luo et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…This controlled drainage approach is further described and simulation results provided in Wahba et al . ().…”
Section: Model Descriptionmentioning
confidence: 97%
“…Crops are grown in Egypt in rotation and the choice of crops for a rotation depends on the soil conditions, crop characteristics, water availability, economic values of crops, current practices and cultural preferences. One of the most common rotations in the Nile Delta is wheat–maize–berseem–cotton (W–M–B–C) (Wahba et al , ). The crop input data required for the DRAINMOD‐S model are the crop planting and harvesting dates, which are shown in Table .…”
Section: Model Descriptionmentioning
confidence: 99%
“…To investigate whether controlled drainage can maintain higher groundwater tables without increasing soil salinity the simulation model DRAINMOD-S was applied to the western Nile Delta. The results showed that controlled drainage has the potential to maintain and even increase yields while increasing irrigation water use efficiency by 15-20% (Wahba et al, 2005). The savings can be obtained with low-cost and easily operated devices.…”
Section: Planning and Designmentioning
confidence: 97%